PONTIANAK WEDDING CENTER - Neri Nuranita; Hamdil Khaliesh; Jawas Dwijo Putro (JMARS: Jurnal Mosaik Arsitektur, 2022)
Marriage is a precious moment for every couple, where they formalize their bond legally according to law, norms, and religion. At a wedding, the venue for the event is one that must be prepared so that the event can run smoothly. Weddings in the city are often held in hotels or multi-purpose halls. This is due to the limited land area of the house so that it is less accommodating to accommodate guests and vehicle parking spaces in addition to showing self-existence or prestige. In addition to the venue for the wedding, the selection of makeup, clothing, wedding decorations, documentation, entertainment, food and drinks for invited guests is something that needs to be prepared. Of the many preparations needed to provide business opportunities in the field of wedding services and supplies. For this reason, the design of the Pontianak Wedding Center is expected to meet the needs of the community and service providers in wedding equipment. The Pontianak Wedding Center design method consists of several stages, namely the idea stage, the data collection stage, the analysis stage, then the synthesis and finally the design. In designing the Pontianak Wedding Center using a contemporary architectural approach. From the design of the Pontianak Wedding Center, it produces a place for weddings and marriage ceremonies, meeting places, management offices, thematic shopping facilities and other supporting facilities. The design of the Pontianak Wedding Center will be a new idea where the wedding building has a thematic shopping center in it.